Technique/Discourse: When Bergson Invented His Cinematograph - Tortajada, Maria (Recherches sémiotiques / Semiotic Inquiry, 2011)
The “cinematographic model of thought” was developed by Bergson in Creative Evolution (1907) after his 1902-1903 lectures at the Collège de France. His appropriation of this device of modernity certainly didn't go unnoticed. Throughout the twentieth century, Bergsonian discourse produced frequently opposing positions on the cinema, making it necessary for the film historian to question the status of Bergson’s cinematographic dispositive. This dispositive, which strictly belongs to philosophical discourse, refers to equipment and procedures whose mechanism is quite recognizable and isn’t solely confined to the device invented by Lumière. Scholars thus need to confront the technical dimension of this dispositive if they are to examine its very singular character. What makes Bergson’s dispositive technical? How does the shift occur from the technical reference to its appropriation by discourse in demonstrative strategies that transform its value? Starting from this case study, this article seeks to address the following question as directly as possible : what does technique become once it enters (philosophical) discourse? Borrowing from the history of techniques outside the specialized literature on cinema, the article also attempts to redefine the web of relations between discourse and technical fact. Finally, it raises the issue of what may be called a user discourse with respect to specialized discourse, emphasizing the predisposition of any discourse for an osmosis of concepts which the epistemology of viewing dispositives can account for.